Metformin promotes anxiolytic and antidepressant-like responses in insulin-resistant mice by decreasing circulating branched-chain amino acids - Juliane Zemdegs (2019)
© 2019 by the authors. All rights reserved. Epidemiological studies indicate that insulin resistance (IR), a hallmark of type 2 diabetes, is associated with an increased risk of major depression. Here, we demonstrated that male mice fed a high-fat diet (HFD) exhibited peripheral metabolic impairments reminiscent of IR accompanied by elevated circulating levels of branched-chain amino acids (BCAAs), whereas both parameters were normalized by chronic treatment with metformin (Met). Given the role of BCAAs in the regulation of tryptophan influx into the brain, we then explored the activity of the serotonin (5-HT) system. Our results indicated that HFD-fed mice displayed impairment in the electrical activity of dorsal raphe 5-HT neurons, attenuated hippocampal extracellular 5-HT concentrations and anxiety, one of the most visible and early symptoms of depression. On the contrary, Met stimulated 5-HT neurons excitability and 5-HT neurotransmission while hindering HFD-induced anxiety. Met also promoted antidepressant-like activities as observed with fluoxetine. In light of these data, we designed a modified HFD in which BCAA dietary supply was reduced by half. Deficiency in BCAAs failed to reverse HFD-induced metabolic impairments while producing antidepressant-like activity and enhancing the behavioral response to fluoxetine. Our results suggest that Met may act by decreasing circulating BCAAs levels to favor serotonergic neurotransmission in the hippocampus and promote antidepressant-like effects in mice fed an HFD. These findings also lead us to envision that a diet poor in BCAAs, provided either alone or as add-on therapy to conventional antidepressant drugs, could help to relieve depressive symptoms in patients with metabolic comorbidities.